Niche and interspecific relationship of alligator weed (Alternanthera philoxeroides) after a hundred years’ invasion in central China - Lanjing Li; Manfred Denich (Heliyon, 2024)
Alligator weed (Alternanthera philoxeroides (Mart.) Griseb.) is considered one of the worst invasive weeds in China. It was introduced to east China in the late 18th century and gradually spread to central China by the 1930s. Over the course of about a century, it occupied a quite lot of wetlands, agricultural ditches, fishery ponds, and croplands in Central China along the Yangtze River. To reveal the ecological characteristics of alligator weed in the agricultural zone, a field survey was contacted in the mid-Yangtze River region of Hubei Province. A total of 72 species of vascular plants were found in 50 alligator weed plots among 6 field sites. Niche overlap analysis was performed for the 25 main species (frequency>5 %) within alligator weed plots. The analysis showed that only 1 % of species pairs had niche overlap values exceeding 0.5, while 57 % of pairs exhibited a value of 0. These findings suggest that, despite a century of presence, alligator weed has not yet fully naturalized in the region. Alligator weed exhibited the widest niche breadth in the field, with a Levins' Index of 40.778 and a Shannon index of 3.796, indicating its strong resource utilization and invasive potential. The niche similarity among the 25 main species within alligator weed plots was notably low, as none of the specie pairs had a niche similarity value exceeding 0.5, with only 3 % having a value above 0.3. These results suggest that there are no native species having the capability to compete in the ecological niche with alligator weed. Species association analysis revealed that all 24 pairs of species with negative correlation involved alligator weed and other species, indicating that the presence of alligator weed negatively affected other species in the communities. Consequently, continued vigilance is required to monitor and mitigate the further invasion of alligator weed and its impact on local vegetation.